Energy Rebound Due to Re-spending. A Growing Concern - Miklós Antal; Jeroen C.J.M. van den Bergh (Austrian Institute of Economic Research (WIFO), 2014)
Energy conservation is widely accepted as an important strategy to combat climate change. It can, nevertheless, stimulate new energy uses that partly offset the original savings. This is known as rebound. One particular rebound mechanism is re-spending of money savings associated with energy savings on energy intensive goods or services. We calculate the average magnitude of this "re-spending rebound" for different fuels and countries. We find that emerging economies, neglected in past studies, typically have substantially larger rebounds than OECD countries. The effect is generally stronger for gasoline than for natural gas and electricity. Paradoxically, strengthening financial incentives to conserve energy tends to increase rebound. This is expected to gain importance with climate regulation and peak oil. We discuss the policy implications of our findings.
Keywords: 330; rebound effect; re-spending; emerging economies; Nachhaltige Energieversorgung; Fossile Energie; Energiequelle; OECD-Staaten; Schwellenländer